2017
DOI: 10.18038/aubtda.332155
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Fly Ash or Cement Amended Sand-Bentonite Mixtures Exposed to Freeze-Thaw Action After Long Curing

Abstract: In construction of landfills, embankments and transportation structures, use of clay-sand mixtures are commonly preferred. To provide stability and enhance engineering properties, stabilization with chemical admixtures is a reasonable approach. Unfortunately, freeze-thaw effect is a significant problem controlling the mechanical behavior of soils in cold regions. Since past studies on strength behavior of clay-sand mixtures stabilized using fly ash or cement exposed to freeze-thaw action is limited, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The difference in UCS between specimens with and without F/T cycles has been used as an index to estimate the durability of soilcrete against freezing conditions [34,49,53,58]. Binders added to the natural soil could resist freezing damage to a certain extent due to the bonds generated between soil particles and clusters [49,50,56,57,76]. Generally, the strength of soilcrete decreased with F/T cycles.…”
Section: Mechanical Properties Of Soilcrete Subjected To F/t Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in UCS between specimens with and without F/T cycles has been used as an index to estimate the durability of soilcrete against freezing conditions [34,49,53,58]. Binders added to the natural soil could resist freezing damage to a certain extent due to the bonds generated between soil particles and clusters [49,50,56,57,76]. Generally, the strength of soilcrete decreased with F/T cycles.…”
Section: Mechanical Properties Of Soilcrete Subjected To F/t Cyclesmentioning
confidence: 99%
“…In Ref. [76], the authors used the UCS test to investigate the effects of F/T cycles on the clay-sand mixed with cement and fly ash. It was concluded that cement-treated soil has a higher resistance to F/T cycles than fly ash-treated soil, which was attributed to the difference in the hydration and pore-filling efficiency.…”
Section: Multiple Binders Used In Soilcrete Subjected To F/t Cyclesmentioning
confidence: 99%
See 1 more Smart Citation